Application of the Probing-Prompting Learning Model to Improve Students' Speaking Skill of Arabic - Thohir, Muhammad; Junaedi, Junaedi; Ummah, Amalia Miftahatul (Graduate Program Magister Manajemen Pendidikan, 2022)
Arabic is a lesson that guides, develops, encourages, and fosters students' language skills. Many students feel insecure and have difficulty in speaking Arabic. Therefore, this paper used probing-prompting learning model to facilitate student’s speaking skill of Arabic. This research used a quantitative quasi experimental design. The results revealed that student’s speaking skill of arabic was very good by applying probing-prompting model. This paper contributes to the arabic teacher use probing-promting learning model to to improve student’s speaking skill of arabic